To solve the equation 2x + 7 = 5x - 23, we need to isolate the variable x on one side of the equation.
First, let's subtract 2x from both sides to eliminate the x term from the left side of the equation:
2x + 7 - 2x = 5x - 23 - 2x
Simplifying the left side gives:
7 = 3x - 23
Next, let's add 23 to both sides to eliminate the constant term from the right side of the equation:
7 + 23 = 3x - 23 + 23
Simplifying the right side gives:
30 = 3x
Finally, divide both sides by 3 to solve for x:
30/3 = 3x/3
Simplifying gives:
10 = x
Therefore, the solution to the equation 2x + 7 = 5x - 23 is x = 10.
2x+7=5x-23
1 answer